Macular toxicity following brilliant blue G-assisted macular hole surgery – a report of three cases - Jindal, Animesh; Pathengay, Avinash; Mithal, Kopal; Chhablani, Jay; Pappuru, Rajeev Reddy; Flynn, Harry W (Nepalese Journal of Ophthalmology, 2014)
Introduction: Brilliant blue G is a new dye used for staining the internal limiting membrane to ease its peeling in cases like a macular hole. Cases: Three patients presented with full-thickness idiopathic macular hole. They underwent pars planavitrectomy, Brilliant Blue G (BBG) stained internal limiting membrane peeling and fluid gas exchange. Observations: Postoperatively,the macular hole closed but foveal thinning and perifoveal hyperpigmentation presumably due to BBG toxicity were observed in all three patients. All of them had a subnormal final best corrected visual acuity. Conclusion:This case series highlights the unusual occurrence of macular toxicity following brillantblue G-assisted macular hole surgery. DOI: http://dx.doi.org/10.3126/nepjoph.v6i1.10779   Nepal J Ophthalmol 2014; 6 (2): 98-101